Computational fluid dynamics analysis of sponge iron rotary kiln. (March 2017) - Gaurav, Gajendra Kumar; Khanam, Shabina
Abstract: 2D CFD model of rotary kiln of sponge iron process is developed to study the effects of angle of inclination, number of rotation and mass flow rate of iron ore on output parameters. Based on grid independent test for temperature profile optimum mesh size is selected. The result shows that optimum angle of inclination, number of rotation and flow rate of iron ore are found as 2.7 degree, 4.8 rpm and 10 kg/s, respectively. At these optimum conditions the % metallization is predicted as 89.5%, which is 3.24% less in comparison to the existing system. The temperature profiles of gas and bed are also found within acceptable temperature limits. The results are compared well with the published work as well as industrial data. Graphical abstract: Schematic of the sponge iron rotary kiln Comparison of bed and gas temperature profiles. Highlights: 2D CFD model is developed for simulation of rotary kiln of sponge iron process. Effects of varying inclination angle, rotation and iron ore flow rate are studied. Optimum conditions are found based on Fe content, temperature profiles. Grid independent test is performed on temperature profiles for optimum mesh size. Temperature profiles of gas and bed are compared well with published literature.